Gauging acceptance of a hepatitis C test by family planning clinic attendees in Glasgow, UK. Issue 4 (1st October 2007) - Sharp, Laura; Hutchinson, Sharon J; Goldberg, David; Taylor, Avril; Carr, Susan
Abstract : Background: In the UK, pregnant women are not offered and recommended a hepatitis C virus (HCV) test because no effective intervention to prevent vertical transmission of HCV exists following conception. Mother-to-child transmission of HCV could, however, be reduced if infected women planning to have children underwent a course of therapy prior to conception. Objective: To determine what proportion of female family planning clinic (FPC) attendees would hypothetically accept an HCV test if they were offered it and to identify the factors associated with such a decision. Methods: Opportunistic sampling was used to recruit 1000 women attending FPCs in Glasgow during 2002/2003. Participants were asked to self-complete a brief questionnaire about HCV and testing. Results: Of 964 participants, 62% reported that they would accept an HCV test if it was offered in the family planning setting and 24% indicated that they were undecided. Only 4% of women reported that they would be offended if offered an HCV test. The highest rates of hypothetical acceptance of an HCV test were reported among those who had ever injected drugs (88%) and those who felt that they were at risk of being infected with HCV (84%). Women who were single [adjusted odds ratio (OR) 1.4, 95% CI 1.1–1.8] and who were of non-white ethnic origin (adjusted OR 2.5, 95% CI 1.0–6.2) were also significantly more inclined to hypothetically accept an HCV test. Conclusion: Selective HCV testing to those women at high risk of HCV infection should be encouraged in the family planning setting.